Exploring the Morphological and Functional Changes in Phaseolus vulgaris L Subjected to Different Durations of Heat-Moisture Treatment - Ridawati, Ridawati; Alsuhendra, Alsuhendra; Ramadani, Muhammad Indera (agriTECH, 2025)
Phaseolus vulgaris L, known as red bean, is a staple food in Indonesia. The temperature sensitivity of red bean limits the applications despite the high starch content. Therefore, this research aims to analyze the effects of heat-moisture treatment (HMT) on the properties of red bean starch, focusing on the functional and morphological characteristics. The effects of HMT (4, 5, and 6 hours at 110°C) were elevated on fresh and dried red bean starch using Completely Randomized Design. The results show that significant alterations were observed in starch properties due to HMT. Water absorption capacity (WAC) varied with HMT duration and fresh bean starch peaked at 4 hours (198.0 ± 0.1%) before declining at 6 hours (159.5 ± 0.7%). In contrast, dried bean starch showed a decrease from the native capacity of 223.5 ± 5.0% to 176.5 ± 5.0% after 6 hours of HMT. Oil absorption capacity (OAC) also changed markedly and fresh bean starch increased from 68.0 ± 2.8% to 85.5 ± 0.7%. Similarly, dried beans increased from 67.0 ± 1.4% to 83.5 ± 0.7% since the effectiveness of HMT enhanced starch interaction with water and oil molecules. In fresh and dry beans, swelling power decreased and increased with prolonged HMT, reaching a peak at 4 hours (8.57 ± 0.15 g/g). However, solubility index decreased in both types following an increase in HMT duration. The morphology of starch granules transitioned from round or elliptical shapes to more polyhedral and irregular forms, reflecting substantial structural changes. In conclusion, HMT effectively modified the functional properties of red bean starch to offer potential benefits for application in food industry.